Internet Dan Media Sosial Sebagai Wadah Promosi Laboratorium Kalibrasi Upt Pengujian Dan Sertifikasi Mutu Barang (PSMB) Medan - Pangestika, Widya; Imsar, Imsar (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2022)
The speed of internet access and the rapid growth of the smartphone industry makes it easier for people to get information. In the field of marketing, this affects how the promotion is done. The use of social media which is actually means for social interaction between online individuals becomes commonly used by companies as a tool for promotion. One of the social media that is often used is Instagram, an application that allows users to share photos and pictures along with short messages with other users. This study discussed how Instagram as a social media can affect consumer intention toward on the use of laboratory services for testing and certifying the quality of goods. The subject of research is UPT PSMB Medan.